PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA PEGAWAIPADA SEKRETARIAT DAERAHKABUPATEN LOMBOK TENGAH - Mastur Mastur; zainal abidin; Alamsyah Alamsyah (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This study was conducted  to determine  the effect of organizational  culture and effectiveness  ofleadership  style  to  motivate  employees  to  work  at  the  Regional  Secretariat  of  Central  Lombok Regency. The problem of motivation is a topic that never ceases to be extracted in order to achieve an understanding of the theoretical with the practical ability in everyday life, especially motivating employees in government agencies.This  research  is  an  associative   causal,  with  137  respondents.   Samples  determined   usingsampling random sampling technique. Data collection toolwas questionnaire  with Likert scale. Data were analyzed by using multiple linear regressions.The results showed that the effectiveness  of the organizational  culture and leadership style has a significant and positive effect on the motivation of employees either partially or simultaneously.Leadership style wasfound  as a dominant  influencing  factor in this research.  This study  found  that  organizational  culture  conducive  and  positive  increase  employee  motivation  to work on, as well as effective leadership will further enhance the work motivation. Harmony and atmosphere that makes employees feel comfortable in working and caring leaders to listen to their employees should be improved so that the employee work motivation will automatically increase.Keywords:    Organizational    Culture,    Leadership    Style    and    Effectiveness    of   WorkMotivation.